Utilization of Water from Void Pit a Through a Water Treatment Plant for Domestic Water Needs at Mess Rayeuk for the Period of July - August 2025 - Weldam, Alfons; Sina, Mhd. Ibnu; Baskoro, Faisal Siddiq (Green Publisher Indonesia, 2025)
The availability of clean water is a vital requirement in supporting mining operations, especially for bathing, washing, and toilet (MCK) purposes at Mess Rayeuk. To date, clean water supply is still entirely dependent on drilled wells, which causes problems such as high operational costs, dependence on groundwater, and environmental risks. This study aims to optimize the use of alternative water sources from Void Pit A through the implementation of a Water Treatment Plant (WTP) as an effort to reduce dependence on drilled wells. The research method uses the Quality Control Circle (QCC) approach with the PDCA (Plan–Do–Check–Action) model. Primary data were obtained from daily water usage records, flow meter monitoring results, and water quality tests in the laboratory, while secondary data came from operational cost reports and groundwater extraction permit documents. The results showed that after the WTP was operational, the use of drilled well water decreased by 57.12%, with the total clean water supply from the WTP reaching 1,089,000 liters in 15 days. In terms of costs, WTP is more efficient with savings of 22.9% compared to the use of drilled wells, and laboratory test results also ensure that the water processed by WTP meets all quality standard parameters according to Minister of Health Regulation No. 32 of 2017. In conclusion, the implementation of WTP has succeeded in increasing the availability of clean water, reducing operational costs, and reducing groundwater exploitation so that it not only provides economic and operational benefits, but also strengthens the company's commitment to supporting environmental sustainability.